Diagnostic Musculoskeletal Ultrasound in the Evaluation of the Median Nerve - Robert C Manske; Chris Wolfe; Phil Page; Michael Voight (International Journal of Sports Physical Therapy)
The median nerve is a crucial structure in the forearm and wrist, responsible for motor and sensory functions. Accurate diagnosis of nerve injury is essential for appropriate treatment planning and optimizing patient outcomes. Although magnetic resonance imaging (MRI) and nerve conduction studies (NCS) are the gold standard for nerve assessment, diagnostic musculoskeletal (MSK) ultrasound offers a portable, real-time, and cost-effective alternative that is gaining traction in rehabilitation and sports medicine settings. MSK ultrasound has emerged as a valuable, non-invasive imaging modality for evaluating median nerve pathology, including carpal tunnel syndrome (CTS), nerve entrapment, and traumatic nerve injuries. This article reviews the utility of MSK ultrasound in evaluating the median nerve injury, including its anatomy, common injury patterns, sonographic techniques, and clinical implications for professional rehabilitation. By integrating MSK ultrasound into clinical practice, providers can improve the accuracy of diagnosis, monitor healing progression, and guide rehabilitation strategies for optimal patient outcomes.